2013
DOI: 10.1002/poc.3247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the structure of nitroxyl radicals on the kinetics of their acid-catalyzed disproportionation

Abstract: Acid‐catalyzed disproportionation of cyclic nitroxyl radicals R2NO• includes the half‐reactions of their oxidation to oxoammonium cations R2NO+ and reduction to hydroxylamines R2NOH. For many nitroxyl radicals, this reaction is characterized by its ~100% reversibility. Quantitative characteristics of acid–base and redox properties of the whole redox triad may be obtained from research of kinetics and equilibrium of this reaction. Here, we have examined the kinetics for the disproportionation of twenty piperidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…A convenient way to accomplish this is to study in detail the acid catalyzed disproportionation of nitroxyl radicals. For many radicals, this reaction is 100% reversible [17,18] (Scheme 2). It includes half reaction of reduction of nitroxyl radicals 1 → 3 and oxoammonium cations 2 → 1, as well as acid-base equilibria of protonation of radicals 1 and hydroxylamines 3.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…A convenient way to accomplish this is to study in detail the acid catalyzed disproportionation of nitroxyl radicals. For many radicals, this reaction is 100% reversible [17,18] (Scheme 2). It includes half reaction of reduction of nitroxyl radicals 1 → 3 and oxoammonium cations 2 → 1, as well as acid-base equilibria of protonation of radicals 1 and hydroxylamines 3.…”
Section: Introductionmentioning
confidence: 98%
“…[17] For other studied radicals, acidity constants pK 1H+ are calculated using the rate constant k 2 0 found for radical 1a. [18] The rate constants of the forward [19] 21 ± 1 [19] ; 18 [17] 51 (1) (3) (4) (2) and reverse reactions of equilibrium (2) depend on the difference between the reduction potentials of cation radicals 1H + to hydroxylamines 3 (E 1H+/3 ) and reduction potentials of oxoammonium cations E 2/1 . Weak dependence of constants k À2 on the nature of substituents R for compounds a-g indicates small changes in the difference E 1H+/3 À E 2/1 for piperidine derivatives.…”
mentioning
confidence: 99%
“…Besides radical V is among the most easily oxidized cyclic nitroxyls {Eº(R 2 N + =O/R 2 N-O • ) 0.79 V [18]} thus providing a high antioxidant activity [8]. Finally, hydroxylamine VII as a base is sufficiently stable against the oxidation with air oxygen and it is possible to prepare its crystals fit for XRD analysis.…”
mentioning
confidence: 98%
“…It should be noted that, while oxoammonium cations such as 11 are important species inferred in many catalytic oxidative processes, only a few oxoammonium salts, mainly of TEMPO derivatives, have been isolated as discrete stable materials [1][2][3] . For fully alkyl-substituted radicals such as 3, it has been shown that decomposition of the oxoammonium salt occurs predominantly via b-deprotonation by a base 1,32 . For 3, the equilibrium between two nitroxides and the oxoammonium ion and hydroxylamine can also be catalysed by acid 1,32 .…”
mentioning
confidence: 99%
“…For fully alkyl-substituted radicals such as 3, it has been shown that decomposition of the oxoammonium salt occurs predominantly via b-deprotonation by a base 1,32 . For 3, the equilibrium between two nitroxides and the oxoammonium ion and hydroxylamine can also be catalysed by acid 1,32 . Other fully a-substituted nitroxides with highly sterically demanding flanking groups may also undergo C-N bond scission 19 .…”
mentioning
confidence: 99%